Experimental Research on the Performance of Heat Pipe Radiation Heating Device Driven by Heat Pump - Ding Ruochen; Xu Shuxue; Ma Guoyuan; Jiang Mingjian (Zhileng xuebao)
In this study, the working principle of a heat pipe radiation heating device driven by heat pump was proposed. The prototype has been developed for testing based on a 1 HP compressor and the operating characteristics of the prototype under the working conditions of indoor temperature from 18 ℃ to 22 ℃, outdoor temperature from -15 ℃ to 0 ℃ are tested in the air enthalpy room. The experimental results showed that the heat pipe radiator can start rapidly and has a uniform temperature distribution. The optimal charge of heat pipe working fluid ratio is 0.1. The maximum heating coefficient of performance (COP) of the system can reach 4.1 under the condition of 22 ℃ indoors and﹣15-0 ℃ outdoors.